Legal Responsibility of Business Actors in Breach of Contract Cases in Online Sales Agreements: A Study of District Court Decisions - Made Dian Sasmitha (Journal of Social Research, 2025)
The advancement of information technology has facilitated online buying and selling transactions, but it has also led to potential breaches of contract (wanprestasi) by business entities, such as the delivery of non-conforming goods, shipment delays, and unilateral cancellations. This article examines the legal accountability of business actors in online sales agreements through a normative juridical approach, analyzing statutory regulations and judicial decisions. The findings reveal that common types of breach include product discrepancies, delayed deliveries, and failure to fulfill delivery obligations despite completed payments. In accordance with Articles 1239–1243 of the Indonesian Civil Code, Law No. 8 of 1999 on Consumer Protection, and Law No. 19 of 2016 on Electronic Information and Transactions, business entities are legally liable for such breaches. Court decisions, such as Decision No. 629/Pdt.G/2020/PN Jkt.Sel, illustrate how judges evaluate the elements of breach based on evidence, the principle of good faith, and consumer loss. This study underscores the necessity of enhancing legal awareness among business actors and strengthening dispute resolution mechanisms to ensure fairness for consumers within the rapidly evolving digital business ecosystem.